2005
DOI: 10.1152/ajpheart.00115.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation during brain activation paradigms

Abstract: Dynamic cerebral autoregulation (CA) describes the transient response of cerebral blood flow (CBF) to rapid changes in arterial blood pressure (ABP). We tested the hypothesis that the efficiency of dynamic CA is increased by brain activation paradigms designed to induce hemispheric lateralization. CBF velocity [CBFV; bilateral, middle cerebral artery (MCA)], ABP, ECG, and end-tidal Pco(2) were continuously recorded in 14 right-handed healthy subjects (21-43 yr of age), in the seated position, at rest and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
8
34
0
1
Order By: Relevance
“…This is the usual assumption made in estimating confidence limits in system identification e.g. [31] but requires further investigation following on from some recent studies on the dynamics of CA [23,32]. In the current work the estimated intra-subject variability can however be interpreted as the dispersion of estimates to be expected if the source of errors were only added noise rather than less tractable physiological variation.…”
Section: Intra-subject Variabilitymentioning
confidence: 88%
See 1 more Smart Citation
“…This is the usual assumption made in estimating confidence limits in system identification e.g. [31] but requires further investigation following on from some recent studies on the dynamics of CA [23,32]. In the current work the estimated intra-subject variability can however be interpreted as the dispersion of estimates to be expected if the source of errors were only added noise rather than less tractable physiological variation.…”
Section: Intra-subject Variabilitymentioning
confidence: 88%
“…Previous analyses that concentrated on the performance of the ARI [25,32,33] have shown large variations over time and sudden drops to zero of this index. Although rigorous studies have not been performed to understand the source of this variability, this may be due to the constraint that the Aaslid's model [15] imposes on the index as it only uses a set of ten filters [25].…”
Section: Intra-subject Variabilitymentioning
confidence: 99%
“…It has been reported that systemic fluctuations related to blood pressure or heart rate-in particular, because of dynamic cerebral autoregulation 63,64 or veins on the brain surface 34 -can influence the NIRS signal. 65,66 In these cases, to extract cerebral blood including systemic signal, we need to use a signal discrimination method that considers the dependence of signal amplitude on S-D distance instead of just the waveform characteristics of the signal.…”
Section: Future Workmentioning
confidence: 99%
“…These results are consistent with studies investigating the dynamic properties of the myogenic component of autoregulation of blood flow in different species and/or other vascular beds. Using transfer function analysis between BP and cerebral blood flow (transcranial Doppler), dynamic cerebral autoregulation was found to operate at frequencies below 0.07 Hz in humans [16][17][18]. The myogenic component of renal blood flow autoregulation has been identified between 0.1 and 0.2 Hz in rats [19][20][21] and between 0.06 and 0.15 Hz in dogs [22] and in the mesenteric circulation of rats, autoregulation operates in a similar frequency range and is most effective at 0.13 Hz [21].…”
Section: Introductionmentioning
confidence: 99%